ADMINISTRATIVE LAW OF UKRAINE: MODERN CHALLENGES AND PROSPECTS OF DEVELOPMENT - Rybchenko S. O. (Taras Shevchenko National University of Kyiv, 2024)
The article examines modern challenges and prospects for the development of administrative law in Ukraine, taking into account the country's recent reforms and European integration efforts.It is noted that the administrative law of Ukraine is one of the main branches of the legal system, which regulates relations in the spheres of functioning of executive power, local selfgovernment, economy, education, health care, defense and others.The problems of state control, administrative-legal relations and the need to improve administrative legislation are analyzed.It has been proven that the further development of administrative law in Ukraine should take place in the direction of establishing a human-centered ideology, overcoming post-Soviet paternalistic approaches, and implementing the best European practices of public administration. This requires not only an update of legislation, but also a change in administrative culture and legal awareness. Administrative law should become a «citizen's right» and not a «state's right». Only under such conditions is it possible to establish Ukraine as a legal and democratic state in which public administration serves the interests of society and every individual.

У статті досліджено сучасні виклики та перспективи розвитку адміністративного права в Україні, враховуючи останні реформи та євроінтеграційні зусилля країни. Зазначено, що адміністративне право України є однією з основних галузей правової системи, яка регулює відносини в сферах функціонування виконавчої влади, місцевого самоврядування, економіки, освіти, охорони здоров'я, оборони та інших. Проаналізовано проблеми державного контролю, адміністративно-правових відносин та необхідність вдосконалення адміністративного законодавства.Доведено, що подальший розвиток адміністративного права в Україні має відбуватися в руслі утвердження людиноцентристської ідеології, подолання пострадянських патерналістських підходів, впровадження кращих європейських практик публічного адміністрування. Це вимагає не лише оновлення законодавства, але й зміни адміністративної культури та правосвідомості. Адміністративне право має стати «правом громадян», а не «правом держави». Лише за таких умов можливе становлення України як правової та демократичної держави, в якій публічна адміністрація служить інтересам суспільства і кожної особи.
АДМІНІСТРАТИВНЕ ПРАВО УКРАЇНИ: СУЧАСНІ ВИКЛИКИ ТА ПЕРСПЕКТИВИ РОЗВИТКУ
Keywords: administrative law; administrative process; globalization; public administration; local self-government.; адміністративне право; адміністративний процес; глобалізація; публічне адміністрування; місцеве самоврядування